A patient case demonstrating the efficacy of benralizumab in uncontrolled severe eosinophilic asthma refractory to omalizumab and mepolizumab treatment - John Davison (Elsevier, 2021)
Severe eosinophilic asthma is associated with a heavy burden and impact on daily living in patients experiencing uncontrolled symptoms, exacerbations, and treatment side effects. This case study reports a 49-year-old woman who presented to the severe asthma center with uncontrolled severe asthma despite multiple maintenance medications and omalizumab treatment. On presentation, the patient had experienced two to three hospitalizations per year, frequent asthma exacerbations requiring courses of oral corticosteroids, and symptoms that impacted her quality of life. Omalizumab was previously discontinued, and bronchial thermoplasty was also unsuccessful. The patient stabilized on injectable steroids and commenced mepolizumab once available on prescription. Owing to continued exacerbations and an inability to reduce steroid treatment without exacerbating, mepolizumab was discontinued and the patient commenced benralizumab (30 mg subcutaneously every 4 weeks for the first three doses, every 8 weeks thereafter) under the sole care of the severe asthma center. Benralizumab treatment resulted in a reduction in steroid treatment, zero asthma exacerbations, improved asthma control and lung function, and a marked improvement in activity levels that allowed the patient to participate in a long-distance running event. Additionally, 7 months following the initiation of benralizumab treatment, her blood eosinophils were completely depleted. These findings support the use of benralizumab in patients with refractory uncontrolled severe eosinophilic asthma despite previous biologic treatment with omalizumab and mepolizumab, as improvements in clinical and patient outcomes, including quality of life, can be achieved in difficult-to-treat cases.